KRITERIA KELIMPAHAN BAMBU LAUT (Isis hippuris) DI PERAIRAN KONAWE SULAWESI TENGGARA - Abdullah Abdullah; Abdul Rauf; Asbar Asbar (Jurnal Pendidikan Teknologi Pertanian, 2019)
Sea Bamboo (Isis hippuris) is a fish species that is protected based on a certain period of time (moratorium). This research was conducted from September to October 2018. This research was conducted with the aim of Knowing the abundance criteria of sea bamboo (Isis hippuris) in the waters of Konawe, The results of this study indicate that: (1). The highest abundance of sea bamboo  located in Toronipa Village with overflow categories. Followed by Bokori Island with a lot categories, Wawohara Village medium category, Saponda Laut Island rare category is rare, and Saponda Island Land rare category.